2021
DOI: 10.21203/rs.3.rs-1037656/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Carriage of mutations R462Q (rs 486907) and D541E (rs 627928) of the RNASEL gene and risk factors in patients with prostate cancer in Burkina Faso.

Abstract: Background Prostate cancer (Pca) is a public health problem that affects men, usually of middle age or older. It is the second most common cancer diagnosed in men and the fifth leading cause of death. The RNASEL gene located in 1q25 and identified as a susceptibility gene to hereditary prostate cancer, has never been studied in relation to prostate cancer in Burkina Faso. The aim of this study was to analyze the carriage of RNASEL R462Q and D541E mutations and risks factors in patients with prostate cancer in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
2
0
0
Order By: Relevance
“…Tese results could be attributed to late diagnosis and the low rate of prostate cancer screening programs in Burkina Faso, highlighting the high PSA levels at diagnosis obtained in our study (mean 642.12 ± 1153.42 ng/ml). Tese levels are almost similar to those obtained (mean PSA of 537 ng/ml et 627.85 ng/ ml) in a previous study in Burkina Faso [29,30]. Regarding the Gleason score, 73.65% of the patients had a Gleason score of 7 or higher.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Tese results could be attributed to late diagnosis and the low rate of prostate cancer screening programs in Burkina Faso, highlighting the high PSA levels at diagnosis obtained in our study (mean 642.12 ± 1153.42 ng/ml). Tese levels are almost similar to those obtained (mean PSA of 537 ng/ml et 627.85 ng/ ml) in a previous study in Burkina Faso [29,30]. Regarding the Gleason score, 73.65% of the patients had a Gleason score of 7 or higher.…”
Section: Discussionsupporting
confidence: 88%
“…Many studies have reported that black men are diagnosed with prostate cancer at a younger age [27,28]. We obtained a mean age of patients at diagnosis of 67.46 ± 8.03 years with an age range of 51 to 81 years, similar to the age range found in Burkina Faso in 2022 and Cameroon (67.8 ± 7.44 years) in 2019 [25,29].…”
Section: Discussionsupporting
confidence: 54%